Constraints on fluid flow pathways from shear wave splitting in and around an active fluid-escape structure: Scanner Pockmark, North Sea. Issue 2 (6th June 2022) - Robinson, A H; Bayrakci, G; Macdonald, C; Minshull, T A; Bull, J M; Chapman, M; Henstock, T J; Callow, B
SUMMARY: Vertical fluid-escape structures observed in seismic reflection data represent an important class of potentially active fluid flow pathways. An understanding of the mechanism of fluid flow in these types of structures is needed to assess the risk of natural gas venting from potential subsurface carbon dioxide storage operations. The Scanner Pockmark Complex is a 22 m deep, 900 × 450 m seabed depression in the North Sea, which actively vents methane, and is underlain by a seismic chimney structure with horizontal dimensions of ∼300 × 600 m. Gas accumulation is evidenced by the presence of bright reflectors at the top of this seismic chimney, at a depth of ∼50 m below the seabed. Here, we analyse seismic anisotropy in these shallow sediments using shear wave splitting observed on ocean bottom seismographs (OBS). Anisotropy varies spatially, with a strength of ∼1–4 per cent, on several OBS located in and around the pockmark complex. By correlating these observations with calculated subsurface P - and S -wave velocities, we show that there is anisotropy present throughout the sediments through which the chimney passes, which are interpreted as relating to syn- and post-depositional glaciomarine processes. However, within the chimney itself the orientation of the fast direction is different to that outside the chimney and the degree of anisotropy is lower. We attribute this difference as indicating that the anisotropy observed within the chimney is associated with the formation and continued presence of the gas migration system, which overprints the background depositional anisotropy.